When microscopy and electrophysiology meet connectomics—Steve Massey’s contribution to unraveling the structure and function of the rod/cone gap junction - Ribelayga, Christophe P.; O’Brien, John (Frontiers in Ophthalmology, 2023)
Electrical synapses, formed of gap junctions, are ubiquitous components of the central nervous system (CNS) that shape neuronal circuit connectivity and dynamics. In the retina, electrical synapses can create a circuit, control the signal/noise ratio in individual neurons, and support coordinated neuronal firing of ganglion cells, hence regulating signal processing at the network, single cell, and dendritic level. Steve Massey and we, the authors, have had a long interest in gap junctions in retinal circuits in general, and in the network of photoreceptors in particular. Our combined efforts, based on a wide array of techniques of molecular biology, microscopy, and electrophysiology, have provided fundamental insights into the molecular structure and properties of the rod/cone gap junction. Yet, full understanding of how rod/cone coupling controls circuit dynamics necessitates knowing its operating range. If it is well established that rod/cone coupling can be greatly reduced or eliminated by bright light adaptation or pharmacological treatment, the upper end of its dynamic range has long remained elusive. This held true until Steve Massey's recent interest for connectomics led to developing a new strategy to assess this issue. The effort proved effective in establishing with precision the connectivity rules between rods and cones and estimating the theoretical upper limit of rod/cone electrical coupling. Comparing electrophysiological measurements and morphological data indicates that under pharmacological manipulation, rod/cone coupling can reach the theoretical maximum of its operating range, implying that under these conditions, all the gap junction channels present at the junctions are open. As such, channel open probability is likely the main determinant of rod/cone coupling that can change momentarily in a time of day-and light-dependent manner.Here we briefly review our current knowledge of the molecular structure of the rod/cone gap junction and of the mechanisms behind its modulation and we highlight the recent work led by Steve Massey. Steve's contribution has been critical towards asserting the modulation depth of rod/cone coupling as well as elevating the rod/cone gap junction as one of the most suitable models to examine the role of electrical synapses and their plasticity in neural processing.